(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The effect of the reaction of the coordination compounds o-aminobenzoic acid, hydroxylamine and cobalt-II nitrate on houseplants "black prince" was studied. The expected results in our experiment consists of the following steps.